Progress or plateau? A 20-year systematic review of self-efficacy among TCFL teachers - Shi, Qian; Zhang, Jing; Zhao, Wei (Frontiers in Psychology, 2025)
This systematic review examined research on the self-efficacy of teachers of Chinese as a foreign language (TCFL) from 2004 to 2024. Guided by social cognitive theory and Bandura’s concept of self-efficacy, 15 empirical studies were synthesized following PRISMA guidelines, employing both qualitative and quantitative analyses. The review identified key factors influencing TCFL teacher self-efficacy, including personal, student, and environmental factors. It further showed that teacher self-efficacy predicts important outcomes such as technology use and integration, career development and retention, and emotional and psychological resources. The findings underscore the need for targeted professional development, supportive institutional policies, and cross-cultural adaptation resources, and they point to future research directions on emerging technologies and diverse teaching contexts.